Frequency of HBV Surface Antigen and Anti - HCV in healthy voluntary blood donars in Swat district - Ahmad, Aziz (Journal of Postgraduate Medical Institute, 2011)
To find out the seroprevlaence of HbsAg and anti HCV among the helathy voluntary blood donors in the district of Swat, NWFP.This cross sectional survey study was conducted at blood transfusion services unit Saidu Group of Teaching Hospital Swat. All voluntary healthy blood donors attending the above services from January 2003 to December 2005 were screened for HbsAg and anti hCV by Acontest device. Seroprevalence of HbsAg and Anti HCV in helathy voluntary blood donors in swat district is relatively low as compared to the prevalence in overall general population of Pakistan. All blood donors should be routinely screened and young healthy non paid donors should be encouraged to donate blood for blood banks.